Prevention of Oral Health Disease : Knowledge and Practices among Pregnant Women in Kuantan, Pahang - Jamani, Nurjasmine Aida; Abd. Aziz, Karimah Hanim; Abllah, Zurainie (2019)
Background: Oral disease in association of pregnancy outcome has been long researched. Most pregnant women perceived that oral disease in pregnancy are expected and considered to be normal. Objective: This study aims to evaluate the knowledge of pregnant women and their practices towards oral disease. Methods: 296 pregnant mothers were recruited from government clinics in Kuantan, Malaysia. A validated and self -administered questionnaire assessing knowledge, attitudes and practices towards oral health was used. Results were analysed by descriptive analysis, chi square test and multiple logistic regression. Results: Most respondents showed poor knowledge on oral health problem with its pregnancy outcome (66.6%) and poor attitude about dental health during pregnancy (53.4%). Half of them had good practice on oral health. Tooth cavity (46.3%) and gum bleeding (29.4%) were the commonest problem reported by them. Only one third of the mothers utilize dental service. Higher level of education was associated with better oral health practice [OR:0.02 CI (1.12,3.92)] Conclusions: Knowledge on the relationship between oral health and pregnancy outcome is still low among pregnant mothers. Utilization of dental service was also low. High level of education is proven to give better oral health care.